Epoxy hybrid composites reinforced with nanodiamond-silica for abrasive applications - Barcelos,Marcos Antônio (2021)
Abstract In this work, a ternary composite of epoxy filled with ND and MS was produced for abrasive applications. Surfactants (oleic acid (OA), sodium dodecyl sulfate (SDS) and Triton TX-100 (TX-100)) were used to improve the particle dispersion and, consequently, the composite properties. The elastic modulus increased up to 76% for the sample with 1 wt% ND and 5 wt% ND using TX-100 (1ND5MS-TX100). Regardless of the filler concentration, the particles did not modify the thermal degradation behavior of the epoxy. Thermogravimetric (TGA) and dynamic mechanical (DMA) analyses suggest a strong particle-matrix interface, also evidenced in scanning electron microscope (SEM) micrographs. The composites presented superior tribological performance. 1ND5MS-TX100 presented a wear rate of 2.19 x 10-3 mm3.Nm-1, 61.3% lower than the epoxy. Also, all composites significantly reduced the roughness of the marble, being proportional to the abrasives concentration. Overall, composites with TX-100 presented improved wear behavior.